Кримінальна відповідальність за кардшейрінг, камкординг та фінансування порушення авторського права та суміжних прав - Волос, Андрій; Volos, Andriy; Волос, Андрей (Видавництво Львівської політехніки, 2018)
У статті проаналізовано останні зміни у кримінальній охороні авторського та суміжних прав, внесені Законом України про державну підтримку кінематографії в Україні. Зокрема розглянуто нові для українського законодавства поняття «кардшейрінг», «камкординг» та «фінансування порушення авторського права та суміжних прав».

In order to properly regulate social relations, including in the field of intellectual property, which are rapidly developing, regulatory and legal acts are subject to constant updating and improvement. In this regard, on March 23, 2017 the Supreme Council of Ukraine adopted the Law on State Support of Cinematography in Ukraine, which, inter alia, amended Article 176 of the Criminal Code of Ukraine, concerning liability for infringement of copyright and allied rights. In particular, Article 176 was supplemented with new for Ukrainian legislation terms, such as «cardsharing», «camcording» and «financing of actions that constitute a violation of copyright and allied rights». Before the legislation did not contain definitions of the concepts of «cardsharing» or «camcording», the scientists only offered their doctrinal definitions. It is difficult to predict the impact of the amendments made on the criminal protection of copyright and allied rights. Therefore, it is necessary to properly investigate and identify possible gaps and inaccuracies in legislation to be able to correct them in time. The main purpose of this article is to study the changes in the legal protection of copyright and related rights, as well as to analyze previously unknown to the legislation of Ukraine concepts. Most citizens do not understand how "cardsharing" and "camcording" affect holders of intellectual property rights as well as the economy of Ukraine as a whole. Moreover, the general public does not know what the terms itself mean. It is not enough simply to prohibit «cardsharing» and «camcording», such prohibitions will not be effective without the recognition by each person of what «cardsharing» and «camcording» are, why they are banned, as well as the liability for committing them. General awareness can be spread with the help of social advertising, trailers before the beginning of films, announcements in cinemas and other public places.

В статье проанализированы последние изменения в уголовном охране авторского и смежных прав, внесенные Законом Украины о государственной поддержке кинематографии в Украине. В частности рассмотрены новые для украинского законодательства понятие «кардшейринг», «камкординг» и «финансирование нарушение авторского права и смежных прав».
Criminal liability for cardhaching, camcorders and financing for violation of copyright and related rights
Уголовная ответственность за кардшейринг, камкординг и финансирование нарушения авторского права и смежных прав
Keywords: кримінальна охорона; кардшейрінг; камкординг; фінансування порушення; аудіовізуальний твір; criminal defense; cardhearing; camcorders; financing violations; audiovisual work; уголовное охрана; кардшейринг; камкординг; финансирование нарушения; аудиовизуальное произведение; 343.533.9